2014
DOI: 10.1371/journal.pone.0098742
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Homeless People in Tehran, Iran, to HIV, Tuberculosis and Viral Hepatitis

Abstract: BackgroundHomeless people are at risk of contracting communicable infectious diseases, as they indulge in risky behaviours and lifestyle. This study was conducted to determine the prevalence of the aforementioned infections and related risk behaviours among homeless people in Tehran.MethodsIn this study a convenience sample of 593 homeless individuals was studied. The ELISA method was used for the detection of HIV, HCV and HBV. Clinical symptoms, sputum cultures, acid fast bacilli smears, and chest X-rays were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
0
23
4
Order By: Relevance
“…Differences in prevalence can be explained, in addition to different endemicity profiles between countries, by variations in the population characteristics and risk behaviors, especially injection drug use. In fact, in this study, the prevalence of injection drug use (8.7%) was low compared to the studies conducted in Iran (27.6%) [15], England (34.0%) [9], and USA (28.2%) [5]. …”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Differences in prevalence can be explained, in addition to different endemicity profiles between countries, by variations in the population characteristics and risk behaviors, especially injection drug use. In fact, in this study, the prevalence of injection drug use (8.7%) was low compared to the studies conducted in Iran (27.6%) [15], England (34.0%) [9], and USA (28.2%) [5]. …”
Section: Discussioncontrasting
confidence: 69%
“…These individuals are at increased risk for hepatitis C, mainly due to sharing needles and syringes [38]. In this study, injection drug use was strongly linked to HCV exposure, as found in the general population of Brazil [4] and several other studies conducted on homeless people [15, 18, 30, 32, 39]. In addition, among men who reported injection drug use, more than half (57.1%) reported sharing drug paraphernalia (data not shown).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In addition, relatively lower prevalence of TB in Iran might be due to lower prevalence of HIV infection (3.4 %) [15]. However, TB prevalence in this study is lower than studies conducted among homeless individuals in USA (6.1 %) [28], Seoul, South Korea (24.86 %) [13], North-eastern Poland (4.13 %) [29] and Colombia (7.9 %) [30], the difference might be due to difference in study design and setting, sample size and laboratory diagnosis method used.…”
Section: Discussionmentioning
confidence: 99%